Life cycle assessment of comparison of substrates for the bioremediation of pentachloroaniline under acidogenic - Hong, Jinglan (The International Journal of Life Cycle Assessment)
Purpose In general, pentachloroaniline (PCA) biodechlorination is specific to the conditions of a system; such conditions include the type and concentration of electron donors and oxidizing agents as well as nutrient availability, pH and temperature. In the bioremediation of contaminated sediments and soil, most researchers have focused on the ability of various electron donors to remove target compounds. However, the amended electron donors and the byproduct of the anoxic/anaerobic systems may cause more environmental impact. Therefore, methods for consistently evaluating the environmental effects of such electron donors and byproducts are highly needed. Accordingly, life cycle assessment (LCA) was carried out to estimate the environmental effect of PCA biodechlorination under acidogenic/methanogenic conditions through laboratory scale experiments. Four scenarios, intended to assess the influence of electron donors on the environment and develop laboratory experimental research, were compared. In these scenarios, four compounds were used : acetate, lactate, methanol and glucose + methanol. Materials and methods The LCA was carried out using IMPACT2002+ to estimate the environmental impact of PCA biodechlorination under acidogenic/methanogenic conditions. To add credibility to the study, sensitivity analysis was also conducted. Results and discussion In all scenarios, the technologies significantly contributed to respiratory inorganics, global warming, as well as increased the adverse impact of nonrenewable energy on the environment. Specifically, the emissions from the electron donor production processes played an important role in the scenarios. PCA dechlorination and methanogenic processes substantially contributed to the aquatic/terrestrial ecotoxicity and global warming, respectively. Optimizing the concentration of amended electron donors and increasing the population size of dechlorinating microorganisms are highly important in reducing the environmental burden by PCA bioremediation. Conclusions Results showed that the methanol scenario was the most suitable option determined in this research. In addition, results indicate amended electron donors can cause fewer environmental impacts in carcinogens and noncarcinogens categories. By contrast, the amended electron donors can significantly increase environmental impacts in respiratory inorganics, global warming and nonrenewable energy categories. Increasing the population size of dechlorinating microorganisms and optimizing the concentration of amended electron donors are highly recommended to reduce adverse environmental impacts.